Pewarisan Karakter Fenotip Melon (Cucumis melo L. ‘Hikapel Aromatis’) Hasil Persilangan ♀ ‘Hikapel’ dengan ♂ ‘Hikadi Aromatik’ - Budi Setiadi Daryono; Nugroho Nofriarno (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2018)
This research aims to develop cultivars with superior phenotypes of melon and high level of productivity. This research used the individual results of crossing between melon  ♀ ‘Hikapel' with ♂ 'Hikadi Aromatik'. The research included qualitative and quantitative phenotype characterization test. The research was conducted in Center of Agrotechnology Innovation University of Gadjah Mada (PIAT-UGM), Kalitirto, Berbah, Sleman, Yogyakarta and Laboratory of Genetics Faculty of Biology UGM on December 2016 until March 2017. Quantitative data analysis used ANOVA testing through PKBT-STAT 2.02 software with Random Complete Block Design (RCBD) method at significance level of 1% and 5%. Melon 'Hikapel Aromatik' has several advantages including oval shape, without net, without lobes, crispy texture, skin-collored yellow RHS (6A), has a 7-14 brix, has volatile aromatic compound and transposon influenced. Based on the results of recapitulation of variance, the characters of 'Hikapel Aromatik' was not uniform.